1971
DOI: 10.1002/anie.197101453
|View full text |Cite
|
Sign up to set email alerts
|

Book Review: Progress in Molecular and Subcellular Biology. Vol. 1. By B. W. Agranoff, J. Davies, F. E. Hahn, M. G. Mandel, N. S. Scott, R. M. Smillie, and C. R. Woese, edited by F. E. Hahn

Abstract: Amsterdam- London-New York 1970. 1st Edit., 506 pp., bound, Dfl. 70.00. "Metastable ions", i.e. ions which decompose on the way from the ion source to the collector, play an important role in the investigation of mass-spectrometric decomposition processes because they yield information on cleaved-off particles. Metastable ions lead to the formation of relatively broad bands in the corresponding mass spectra. However, the low intensity of such bands makes them difficult or impossible to detect.To facilitate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…3. The Au C carbene bond length (1.977(2)Å) in 20 is nearly identical to the Au-C separations in related gold(I) carbene complexes bearing the benzimidazolin-2-ylidene ligand [33,34]. The Au-Cl bond length (2.2814(6)Å) also falls in the range previously reported for complexes of the type [AuCl(NHC)].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…3. The Au C carbene bond length (1.977(2)Å) in 20 is nearly identical to the Au-C separations in related gold(I) carbene complexes bearing the benzimidazolin-2-ylidene ligand [33,34]. The Au-Cl bond length (2.2814(6)Å) also falls in the range previously reported for complexes of the type [AuCl(NHC)].…”
Section: Resultssupporting
confidence: 76%
“…confirmed by NMR spectroscopy. The resonance for the carbene carbon atom in 20 was observed at δ = 181.5 ppm in the 13 C{ 1 H} NMR spectrum, which is a value typical for complexes of the type [AuX(NHC)] (X = Cl, Br) bearing a benzimidazolin-2-ylidene ligand (δ = 175.8-181.2 ppm) [33]. The N-protecting group is still present and can be detected by the resonance for the carbonyl carbon atom at δ = 198.7 ppm in the 13 C{ 1 H} NMR spectrum.…”
Section: Resultsmentioning
confidence: 93%
“…11 Even though polynuclear metal complexes have become popular in recent years owing to their augmented catalytic activity 12 compared to 30 their mononuclear counterparts, examples of such complexes with higher nuclearity containing MIC donors remain rare. 13 Recently, we showed that a di-substituted phenylene bridged bistriazolium salt after deprotonation reacts to yield a dinuclear Ir III complex with additional cyclometalation of the central phenyl 35 ring (Fig. 1).…”
mentioning
confidence: 99%
“…Upon complexation the resonance for α-hydrogen atoms of the pyridine ring (δ = 8.99 ppm) appeared more downfield shifted compared to their corresponding resonance in free pyridine (δ = 8.62). The 35 characteristic resonance for the Ctrz-Pd carbon atoms was observed at δ = 133.1 ppm in the 13 C{ 1 H} NMR spectrum of complex [4]. This resonance is slightly downfield shifted from the C5H resonance of the precursor triazolium salt 2 (δ = 129.2 ppm).…”
mentioning
confidence: 99%
“…The most common ring fusion is of course the annulation of a benzene ring to the C4-C5 bond of the NHC (A, Fig. 1), and indeed a plethora of applications have been disclosed based on the benzimidazole ring structure [23][24][25]. Fused systems that involve one of the imidazole nitrogen atoms (B, C, Fig.…”
Section: Introductionmentioning
confidence: 99%